Pengendalian Putaran Kipas Ventilator pada Smart Smooking Area Menggunakan Mikrokontroler At Mega 8535 dan Sensor Gas MQ7 - Pradika, Ganis Rama; Sumardi, Sumardi; Setiyono, Budi (Departemen Teknik Elektro, Universitas Diponegoro, 2010)
The higher the risk of poisoning for passive and active smokers if they smoked in a closed room. More than 4,000 chemicals and carcinogens contained in cigarettes would be more dangerous as cigarette smoke trapped in confined spaces. Poisons can enter the body in the maximum amount and in a short time. Leaving the window open space will not solve the problem. Cigarette smoke is often blew back into the room and continue to stay in the room for hours. In this final project, designed a special room to smoke a smart, using a special ventilator that will absorb the smoke of ciagrette combustion. Ventilator will do the absorption of gases from burning cigarettes based on the many levels of CO gas in the room. Control is performed by the microcontroller ATmega 8535 using Proportional Control method based on carbon monoxide gas sensor MQ7. Based on tests performed, it is known that proportional control with Kp=0.625 can produce a pretty good system response.Â Keyword:Â cigarette smoke, microcontroller ATmega 8535, proportional control, carbon monoxide gas sensor MQ7